129 Association of adverse ventricular remodelling and gender in aortic stenosis. (5th June 2017) - Singh, Anvesha; Chan, Daniel; Ng, Leong; McCann, Gerry
Abstract : Introduction: Previous echocardiography studies have demonstrated smaller left ventricles(LV) with more hypertrophy and concentric remodelling in females with Aortic Stenosis (AS) compared to males. However, more recent cardiac magnetic resonance(CMR) studies have shown lower LV mass and mass/volume in females. We utilised CMR to assess myocardial perfusion and tissue characterisation, in addition to remodelling and function, and looked at biomarkers of fibrosis (Syndecan-4 and MMP-3) in male and female patients. Methods: Subjects with asymptomatic moderate to severe AS (2?of: aortic valve area <1.5 cm 2, peak gradient >36 mm Hg or mean gradient >25 mm Hg) were recruited in this prospective, multi-centre, observational study. All patients underwent venepuncture, echocardiogram and a comprehensive stress CMR. Results: 174 patients (133 male) were recruited. Females were slightly younger but there was no difference in resting haemodynamics, co-morbidities or AS severity between the genders (Table 1). Male patients had significantly higher LV volumes and mass, with more concentric remodelling, lower systolic (LV ejection fraction, longitudinal and circumferential global peak systolic strain) and diastolic function (longitudinal and circumferential peak early diastolic strain rates) than females. Late gadolinium enhancement (LGE) was more prevalent (51.1% vs . 34.1%, p=0.038) and extent of LGE was also higher in males, as was Syndecan-4 and MMP-3 levels. Extracellular volume (ECV) was marginally higher in female patients. Stress and rest myocardial blood flow (MBF) were significantly lower in males, with no difference in myocardial perfusion reserve. Conclusions: Male patients with AS have more concentric remodelling, worse cardiac function and more fibrosis than females, with biomarkers associated with fibrosis being significantly higher as well, for a similar degree of AS.